ПЕДАГОГІЧНИЙ ПРОЕКТ-ДІЯЛЬНІСТЬ ТВОРЧА (Педагогіка вищої та середньої школи, 2009)
Creative activity is considered in the article, as one of basic qualities of personality in the process of preparation of future teacher of physics.